Porfirias agudas y polimorfismos de las enzimas que metabolizan fármacos - Sánchez Temiño, Victoria Emilia (2019)
Acute porphyrias (AP) are a group of hepathic pathologies characterized by the accumulation of porphyrins and their precursors. They usually manifest at puberty (more\noften in women), and include the New Acute Porphyria (NAP), Acute Intermittent\nPorphyria (AIP), Variegata Porphyria (VP) and the Hereditary Copro Porphyria (HCP) (Thunell et al., 2007). All of them have sudden neurovisceral manifestations, which are\ncommonly known as acute attack or crisis, which are often confused with other\npathologies. These attacks are triggered by exposure to different factors such as fasting, stress, hormones and commonly used medications. Many hypotheses try to explain the\nvariability in the prediction of the porphyrinogenicity of drugs, among which is the genetic polymorphism of the CYP-450 enzymes. In the this work we wanted to verify if the difference in the triggering or not of the acute crises in AIP patients was given by some of the most frequent polymorphisms and clinical significant of the enzymes of the CYP3A\nfamily (CYP3A4 * 22 and CYP3A5 * 3), or even by a difference in the expression of them, given by the AKR1D1. Also, the allelic and phenotypic frequencies of the polymorphisms analyzed were determined for argentinian population with and without\nAIP.\nResults: Both allelic frequencies and genotypic frequencies found in the AIP population are very similar to those of the healthy argentinian population. So when analyzed statistically with the X2 test (p <0.05), it was not a surprise founding out that there is no\ntrend of the AIP population to any SNP. Therefore, the genetic polymorphisms analyzed do not explain the interindividual variability that exists in these patients when an acute crises arrise. Another interesting conclusion obtained from this study is that there is a\nsignificant amount of extensive metabolizers compared to poor metabolizers in the\nhealthy argentinian population. This is extremely important when adjusting the dose of numerous drugs that are metabolized by this path, since these patients may be receiving or have received at first a subtherapeutic dose for their threatment.